PERLINDUNGAN INDUSTRI DALAM NEGERI DARI PRAKTIK DUMPING - Dewa Gede Pradnya Yustiawan (Universitas Pendidikan Nasional, 2018)
Dumping in international trading is an unfair competition which is commonly adopted by the entrepreneurs, that is by selling their product abroad with lower price then in domestic, in attention to have more customer. The strategy of dumping which is done by the entrepreneur gives an effect of financial loss to the domestic industries that produce the similar product. The problems are how is the control of protection for the domestic industries that produce the similar product, what is the measurement in establishing the financial loss for the domestic industries from the practice of dumping, and what effort can be done by the domestic producer who are suffered a financial loss because of the practice of dumping. The result of this research show that the regulations of the domestic industrial protection from the practice of dumping are the regulation in GATT and WTO and national law regulation. The criteria for the measurement in stating the financial loss of the domestic industries which produce the similar product from the practice of dumping are the financial loss, the threat of a real financial loss wich will be faced by the domestic industries that produce the similar product and the obstruction of the development of the domestic industries. The effort to avoid the practice of dumping that can be done by them is to follow the government procedures which have been stated in the government regulation No. 34.Keywords: International Trading, Protection Industries, Dumping